Zambia : Can Financial Incentives Improve the Last-Mile Delivery of Textbooks? - Hong, Seo Yeon (World Bank, Washington, DC, 2020)
Zambia has invested heavily on education with an allocation of about 20 percent of the government budget, but this investment has not translated into better student learning outcomes in primary education. Among the main reasons for this is the severe shortage of learning materials, particularly textbooks in both English and local languages. A public expenditure review of the Zambian education system has shown that 91 percent of schools lack textbooks and on average five to six pupils share less than one textbook, including textbooks in local languages To address this shortage, the REACH Trust Fund provided a grant to investigate the factors related to the availability of textbooks in schools and to evaluate a set of financial incentive mechanisms for improving the last-mile delivery of textbooks. The questions that the research set out to answer were: What is the current status of textbook distribution in Zambia and what are the factors that influence their availability? Do financial incentives have any impact on textbook distribution and availability? What kind of financing scheme might be effective in improving the last-mile delivery of textbooks? Does providing information to schools about textbook availability increase the numbers that are available in schools? A study was conducted in 2018–2019 with the objective of answering these questions. It focused on textbooks procured for use in Zambian literacy and English courses for students in grade two in 2016 and grade four in 2018. The study surveyed 243 schools in 27 districts in Zambia that had not received grade four Zambian language literacy course books until July 2019 as a result of the severe resource constraints that they were experiencing. The study used the difference-in-difference estimation methodology to identify the causal links among the factors contributing to availability and delivery of textbooks to schools.